PEMBERIAN MASKER HIJAB KAIN GRATIS DAN SOSIALISASI CARA PENGGUNAAN MASKER KAIN DI KECAMATAN BENGKONG - Maya Marsevani; Al Ridho Wahyudi; Dandhytya Andrea Puspa; Diana Rosmery; Fitra Abdi Agustian; Kamelia Kamelia; Larassaty Vitrian; Roma Elisabeth Manurung; Siti Fatimah Azzahroh; Syafira Nur Faatihah (National Conference for Community Service Project (NaCosPro), 2020)
The use of masks could be an alternative when people went outside. It helped people to obey the protocol in this pandemic situation. Cloth face masks were offered for women, especially those who wear hijab in Bengkong. It was the main objective of this scientific writing. The purpose of this activity was to provide women’s convenience who wear hijab. Observation, a set of questionnaires, and interviews were used to collect the data. After observing the community in Bengkong, the writers provided cloth face masks that were suitable for women, especially those who wear hijab, and deliver them to the community.